Tradisi Tepuk Tepung Tawar Dalam Perspektif Islam Masyarakat Melayu Riau Di Desa Pangkalan Nyirih Kecamatan Rupat Kabupaten Bengkalis - Mariatik, Mariatik; Maizatul, Maizatul; Jailani, Ahmad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The Tepuk Tepung Tawar tradition is one of the traditional customs of the Malay community, especially in Rupat District, Pangkalan Nyirih Village. Fresh flour is divided into two types, namely in events such as weddings, haircuts, circumcision, erection of houses and moving. at the same time Goods or equipment purchased In general, for example cars, motorbikes, and canoes. Malay society is a society that is passionate about upholding cultural values as a whole, including truth, justice, and respect for all differences. Especially the Malay community in the village of Nyirih Base, the people really care about and uphold customs. This study aims to find out how the Flour Tradition is in Pangkalan Nyirih Village, Dusun V Sei Cuna, Rupat District, Bengkalis Regency, and to find out how the flour tradition is from an Islamic perspective. Qualitative field research is the approach taken. As a result, data will be collected through interviews with community leaders (traditional leaders) in Pangkalan Nyirih Village, Rupat District, Bengkalis Regency with the title Bargaining Tradition in the Islamic Perspective of the Riau Malay Community. This research is included in the analysis description research. In this study, researchers used critical analysis or also known as critical discourse analysis. In this method, the data is processed from the perspective of the researcher by examining the theoretical weaknesses of the data findings